Komunikasi Pemasaran Terpadu UMKM Area Wisata Tugu Keris Siginjai di Era New Normal - Ardiyansyah Ardiyansyah; Fahrizal Fahrizal; Adila Solida (Universitas Batanghari Jambi, 2022)
Many Micro, Small and Medium Enterprises (MSMEs) both in the production sector and in the service business sector have been hit by various challenges due to the COVID-19 pandemic. Among these challenges are a significant decline in turnover, a decrease in customers, difficult to obtain raw materials, and challenges to marketing activities due to government policies related to limiting public interaction and also implementing health protocols throughout Indonesia, including the tourist area of Tugu Keris Siginjai. Jambi City. Currently, MSME actors in the Tugu Keris Siginjai tourist area are faced with the era of a new order or what is known as the new normal. The current New Normal era provides opportunities and challenges for MSME actors to rebuild their businesses which had slumped during the pandemic. This research was conducted with the aim of analyzing integrated marketing communications for SMEs in the Tugu Keris Siginjai Tourism Area, Jambi City in the new normal era. The researcher uses a qualitative research approach to explain the integrated marketing communication carried out by MSMEs in the new normal era which is described in the form of words and a comprehensive picture. From the results of this study it was found that the adaptation of the concept of integrated marketing communication in the new normal era by MSMEs in the Tugu Keris Siginjai tourist area in Jambi City includes elements of advertising, direct marketing, public relations and sales promotions that have not been maximally implemented, this is due to the limited budget for carrying out activities. Integrated marketing communication, especially in the current new normal era, so that not all components or elements of integrated marketing communication can be applied.